DIGITAL TRANSFORMATION OF MOSQUE DA’WAH: ORGANIZATIONAL LEARNING AND INNOVATION IN THE DIGITAL AGE - Thoha, Ahmad Faiz Khudlari; Ibrahim, Muh Syahril Sidik (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2023)
Mosques play a crucial role in religious development, prompting several to enhance their management systems and religious activities through digital transformation. This study critically examines the digital transformation in da'wah at Masjid Al Irsyad, integrating organizational learning theory and contemporary digital innovation. Employing a case study methodology, the research identifies five key dimensions of transformation: the development of innovative online da'wah initiatives, strategic modifications in da'wah methodologies, increased participant engagement, comprehensive training in multimedia, and the establishment of sustainable financial frameworks. Theoretically, the study enriches our understanding of integrating traditional religious practices with modern technology. Practically, it highlights the strategic use of social media for broader da'wah dissemination, the creation of responsive educational programs, and the implementation of sustainable financial models. These insights are crucial for religious organizations aiming to harmonize traditional values with the digital age's demands.